2009
DOI: 10.1007/s10529-009-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression and characterization of recombinant prefoldin from hyperthermophilic archaeum Pyrococcus furiosus in E. coli

Abstract: Prefoldin is a hexameric chaperone that has been identified in eukaryotic cells and in Archaea. E. coli cells over-expressing the prefoldin gene from the hyperthermophilic, archaeum, Pyrococcus furiosus, grew well at 48 degrees C while control cells were unable to grow above 46 degrees C. The isolated and purified Pfu-prefoldin (specially the beta subunit and the prefoldin) thermally protected the activity of lysozyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…For instance, PFDN expression protects against organic solvents toxicity by sequestrating unfolded proteins and thus cooperating with the bacterial chaperone systems to reduce the protein stress caused by exposure to these types of solvents ( Okochi et al., 2008 ). It also increases the tolerance to hyperthermia in these organisms, consistent with the role of archaeal PFDN in preventing protein aggregation and favoring a proper protein folding ( Chen et al., 2010 ) ( Figure 2 ). PFDN, unlike other archaeal chaperones, also rescues the cell growth inhibition caused by antibiotic (aminoglycoside) toxicity, probably through a decrease in the protein folding aggregation caused by this agent ( Peng et al., 2017 ).…”
Section: Introductionsupporting
confidence: 75%
“…For instance, PFDN expression protects against organic solvents toxicity by sequestrating unfolded proteins and thus cooperating with the bacterial chaperone systems to reduce the protein stress caused by exposure to these types of solvents ( Okochi et al., 2008 ). It also increases the tolerance to hyperthermia in these organisms, consistent with the role of archaeal PFDN in preventing protein aggregation and favoring a proper protein folding ( Chen et al., 2010 ) ( Figure 2 ). PFDN, unlike other archaeal chaperones, also rescues the cell growth inhibition caused by antibiotic (aminoglycoside) toxicity, probably through a decrease in the protein folding aggregation caused by this agent ( Peng et al., 2017 ).…”
Section: Introductionsupporting
confidence: 75%
“…It may because of the protection from HSPs is only short-acting [12] that once the duration of thermal stress is enhanced, the cells ultimately undergo cell death. Although the overexpression of HSP has been applied to improve the thermotolerance [49,50], the effects are not ideal. We assumed that preventing protein misfolding by OSR is more important than the repair by HSR after damage.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding prefoldin, chaperonin (HSP60), sHSP, and extracellular α-amylase from P. furiosus (PFA) were PCRamplified from plasmids constructed in previous studies (Chen et al 2006(Chen et al , 2010. Primers used to amplify these g e n e s w e r e a s f o l l o w s : p r e f o l d i n : s e n s e , 5 ′ -GCCCATGGAAAACAATAAGGAAT-3′ (NcoI underlined); antisense, 5′-ACGCGTCGACGGAGCTCGAATTCTCATC-3′ (SalI underlined); HSP60: sense, 5′-ACTATCATATGGC CCAGTTAGCAGGC-3′ (NdeI underlined); antisense, 5′-CAGCTCGAGCTTGCTGGCAGCGATGAC-3′ (XhoI underlined); sHSP: sense, 5′-GCCCATGGTTCGTCGTATC-3′ (NcoI underlined); antisense, 5′ -AACG TC GAC TATTCAACTTT AACTTC-3′ (SalI underlined).…”
Section: Constructions Of Recombinant Plasmidsmentioning
confidence: 99%
“…Previous studies indicated that archaeal prefoldins were able to protect the aggregation of diverse heterogeneous proteins (Iizuka et al 2008;Leroux et al 1999;Laksanalamai et al 2006;Okochi et al 2002;Lundin et al 2004;Hongo et al 2012). Furthermore, overexpression of prefoldin from hyperthermophilic archaea was able to efficiently increase tolerance of E. coli hosts to different environmental stresses, such as the presence of an organic solvent (Okochi et al 2008) or high temperature (Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%